Cycling speed and torque of knee extensors & flexors muscles of cyclists as parameters of talent & speciality identification - Porta, J.; Mas, J.; Rafols, X.; Izquierdo, E.; Aliaga, J.; Ramia,C. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
The results show that the MRP is significantly higher (p< 0,01) in the sprinters than in the other groups studied. As can be expected, in absolute values (Nm), the MICF at 60º/s are significantly higher in the sprinters (values not shown). But in relative values (Nm over body weight) we didn't observe significant differences with the long distance cyclists of high level. The sprinters show the best correlations with the index FLEX./EXT. It's important to notice that, this correlations are higher as the angular speed increases